The Issue of Historical Works in American Literature (Global Journal of Human-Social Science, 2020)
This article discusses the issue of literary perception of historical reality and the creation of a mature work as one of the constant problems of literature, it is about paying special attention to comparative-typological analysis of the unity of form and content, composition and plot, system of characters, historical truth and to the fiction in the study of historical works in today's globalization.The article provides an analysis of advanced examples of American literature, information on folk art thinking and cultural development. The poetics of the work of art, in particular, the approach of how the composition of historical works is solved, the typology of characters, the scientific study of the problem of the genre together form the basis of the article.
Keywords: historical story; fiction; local; historical reality; folklore; memoir; artistic-philosophical; reflistic image; plot